Speech coding effects on recognition accuracy for TIMIT - Nachiappan, Nachiappan (2007)
TIMIT is a corpus of phonemically and lexically transcribed speech of American English speakers of different sexes and dialects. Each transcribed element has been delineated in time. TIMIT was designed to further acoustic-phonetic knowledge and automatic speech recognition systems.